What happened in Cyprus - Athanasios Orphanides (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
This policy letter sheds light on the economic and political backround in Cyprus and provides an analyses of the factors which lead to an intensification of the crisis there. It discusses the severe consequences of the errors made in the recent establishment of an adjustment program for Cyprus by the Europroup for European economic management as a whole.
urn:nbn:de:hebis:30:3-294834
Keywords: 330; financial crisis; troika; Cyprus